Zein‐based composites in biomedical applications. Issue 6 (27th March 2017) - Demir, Merve; Ramos‐Rivera, Laura; Silva, Raquel; Nazhat, Showan N.; Boccaccini, Aldo R.
Abstract: Considerable research efforts have been devoted to zein‐based biomaterials for tissue engineering and other biomedical applications over the past decade. The attention given to zein‐based polymers is primarily attributed to their biocompatibility and biodegradability. However, due to the relatively low mechanical properties of these polymers, numerous inorganic compounds (e.g., hydroxyapatite, calcium phosphate, bioactive glasses, natural clays) have been considered in combination with zein to create composite materials in an attempt to enhance zein mechanical properties. Inorganic phases also positively impact on the hydrophilic properties of zein matrices inducing a suitable environment for cell attachment, spreading, and proliferation. This review covers available literature on zein and zein‐based composite materials, with focus on the combination of zein with commonly used inorganic fillers for tissue engineering and drug delivery applications. An overview of the most recent advances in fabrication techniques for zein‐based composites is presented and key applications areas and future developments in the field are highlighted. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1656–1665, 2017.